Developing a ubiquitous tourist guide - Moura, Humberto; Costa, Cristiano André da; Rigo, Sandro José; Silva, Eduardo Ferreira; Barbosa, Jorge Luis Victória; Silveira Jr., Luiz Gonzaga da; Wichman, Matheus; Bruscato, Underlea (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
In the tourism area, the use of mobile devices brings significant benefits, considering the associated mobility, the instant access and the quality of the tourist information provided. One of the applications in this field is the electronic tourist guide, which provide information to tourists to better enjoy their trip. In this perspective, this work proposes a model that uses mobile and ubiquitous tourism concepts to improve tourist experience. We had developed a prototype for iOS focused on the Caminhos de Pedra tourist itinerary, in Bento Gonçalves / Rio Grande do Sul. Using this prototype, we carried on two evaluations, regarding the ontology proposed and usability. As a result, we could verify that the proposed model helps people to better experience their trips.